Alexandra-Maria Vrînceanu, Feminist Ideology and Translated Literature, Iaşi: Institutul European, 2024, 244 p. - MUDURE, Mihaela (Studia Universitatis Babeș-Bolyai Philologia, 2025)
The young scholar Alexandra-Maria Vrînceanu has an extensive experience as a freelance interpreter and certified translator at Cartea Românească Publishing Press and Black Swan Publishing Press. Since 2019 Vrînceanu has been teaching seminars and practical courses on translation, discourse analysis, and English grammar at the Faculty of Letters of “Alexandru Ioan Cuza” University in Iaşi, Romania. The present study on feminist ideology and the process of translating literature was initially Vrînceanu’s doctoral thesis which she successfully defended in 2023. This piece of scholarship is extremely interesting from several points of view. Firstly, the connection between translation and gender has already been approached as a feminine or feminized activity. In other words, translation has been associated with stereotypes of women’s traditional condition. Translation is subordinated to the source text, it depends on the source text that has the authority and the power of a husband in traditional matrimony, translation is always under the suspicion of treason and infidelity. If it is beautiful, it is unfaithful, and if it is faithful, it is bland and simple. On the other hand, historically, translation was an opportunity for the woman writer to confront the public space, to practise a sort of veiled authorship that was much more acceptable than overt authorship.